Improving Service Level Engineering An Intuitionistic Fuzzy Approach - Schütze, Roland (Fuzzy Management Methods, 2018)
This book examines how fuzzy methods can be employed to manage service levels in business and IT alignment. It starts by mapping the dependencies of service level agreements, coming up with gradual and bi-polar concepts to eventually classify the level of coupling by intuitionistic fuzzy sets. The second part presents an approach to analyze the impact of service failures using intuitionistic fuzzy methods (IFSFIA). Lastly, the third part of the book extends the concept towards business and IT-aligned service-level engineering and provides two use cases.